Janta party experiment - Limaye, Madhu (Delhi B. R. Publishing, 2024)
This volume deals with an important stage in our post-independence politics. After almost three decades of uninterrupted Congress rule, the Congress began to develop strains which led to its division in 1969 and 1978. The impetus for these splits was provided by a curious mixture of Indira Gandhi$1 (Bs overweening personal ambition and her desire to implement what she considered to be a heroic plan to resuscitate the fortunes of the Congress which were on decline and, later, in total eclipse. The disqualification of Indira Gandhi in an election petition in 1975 frightened her and she destroyed the democratic institutions in an effort to stick to her office. The book discusses her reprehensible scheme to create an authoritarian state. It also reveals how her curious craving for legitimacy led her to hold a general election in 1977, and how the opposition parties, propelled into unity by the instinct of self-survival and supported by the masses, defeated her and reestablished democracy by undoing the dangerous constitutional changes made in 1975-76. The Janata Party and its Governments were, however, riven by three social con-traditions. Superimposed on these social conflicts was the attempt of the RSS Pariwar to preserve its identity, and capture the Party and its Governments. The Janata Party was caught in the crossfire of personal ambitions and egos, the social conflicts and the Sangh Pariwar$1 (Bs drive to capture total power through its policies of shifting alliances. This well-documented book by a participant is a highly insightful study of a crucial phase of contemporary history. It is a great merit of this work that although it is an insider$1 (Bs account it aspires to and achieves objectivity in the unfolding of the dramatic story of the rise of the Janata Party Government, and the crises and misfortune which dogged it from its inception. Madhu Limaye (b. 1 May 1922), the most prominent and distinguished among the Socialist Movement$1 (Bs younger leaders.s
Keywords: Polity; Government; Democractic Government